Bangsa Malaysia Narrative: Knowledge, Indigeneity and Nation-state in a Diverse Society (International Online Journal of Language, Communication, and Humanities (INSANIAH), 2020)
The political stability of a nation is related to the development of its nation-state. However, the economic progress of a country is the main basis of measurement. Economic growth and societal well-being are the concern of the newly elected government and the political party winning in the election. Even though most of the post-colonial countries have gained independence, these countries are integrated into the world capitalist system, facing globalisation and exposed to the digital revolution, where not just monetary, information and technology cross-national borders, but aslo manpower from super-diverse socio-cultural origins and worldviews. Thus, if ethnic and religious differences in the society are politicised, especially during times of economic crisis and political campaigning, social tension will take place and eventually, the nation will not be politically stable. The ethnic and religious contestations among the groups affected need to be studied not just solely on the influence of these dimensions as primordial and their social inequalities to the sources of the societal materials but also their importance in defining the political sphere with their interpretation of their own nation-of-intents to gain the political power to rule the country. The contemporary political crisis faced, especially in the aftermath of the General National Election of 2018, has forced researchers to dwell their understanding beyond the importance of ethnic origins but be concerned of ethnicity as it relates to nationalism, nation-building and the nation as the roots of the underpinning political problem being faced. Understanding, explaining and managing the varied nation-of-intents need to be given top priority to ensure national unity, national-building and political stability as the national ultimate agenda of the nation. Sustainable development agenda of the country cannot be separated from the concerns for national unity, nation-building and political stability.
Keywords: Nation Narrative; Nation-State; Nation-of-Intent; Ethnic Group; Post-Colonial Society